Evaluation of the Depok City KB Safari Program in 2025 - Al Silva Nur Aniza; Rini Kundaryanti; Rosmawati Lubis (GLOBAL HEALTH SCIENCE GROUP, 2025)
The Family Planning (KB) Safari Program is a government initiative aimed at increasing the use of long-term contraceptives to control population growth and improve family welfare. However, challenges remain, such as social stigma, lack of family support—especially from husbands—and varied public perceptions regarding contraceptive methods. This study aims to evaluate the implementation and effectiveness of the KB Safari Program in Depok City in 2025, as well as to identify supporting factors and obstacles in the program’s execution. This study employs an evaluative approach with a qualitative descriptive method aimed at exploring facts and assessing the success of the Safari Family Planning Program in the Depok City area. Informants were selected using purposive sampling and consisted of three main categories: one key informant, the Head of DP3AP2KB Office; five primary informants including field officers and implementing midwives; and seven additional informants comprising cadres and participants/acceptors of the Safari Family Planning Program. Data collection was carried out through in-depth interviews, participatory observation, and document studies, with thematic analysis using NVivo software. Research ethics were prioritized, including informed consent, data confidentiality, and the participants' right to withdraw during the interview process. The KB Safari Program was found to operate effectively, positively impacting increased community participation in using contraceptives, particularly long-term methods such as IUDs and implants. Success factors included cross-sector collaboration, efficient scheduling, easily accessible service locations, and comprehensive, responsive education tailored to community needs. Major challenges involved negative perceptions, insufficient spousal support, and the need for enhanced human resource capacity. The KB Safari Program in Depok City is effective in reducing birth rates and raising awareness of family planning. However, strengthening is needed through improved training for implementers and optimized socialization efforts targeting husbands and families.